PENGEMBANGAN MODEL BIMBINGAN KELOMPOK DENGAN TEKNIK SIMULASI UNTUK MENINGKATKAN KECERDASAN EMOSI SISWA (Jurnal Bimbingan Konseling, 2012)
Masalah dalam penelitian ini adalah bagaimana mengembangkan bimbingan kelompok  dengan teknik simulasi. Penelitian in menggunakan pendekata Penelitian ini menggunakan metode penelitian dan pengembangan (research and development). subjek penelitian adalah 10 siswa kelompok kontrol dan 10 siswa kelompok eksperimen yang ditentukan  dengan teknik stratified proporsional random sampling. Validasi penelitian pengembangan ini dengan para ahli bimbingan dan konseling, dan para paktisi / konselor serta teman sejawat di SMP BAE Kudus. Hasil secara umum dalam penelitian ini menunjukkan bahwa model bimbingan kelompok dengan teknik simulasi efektif untuk meningkatkan kecerdasan emosi sis-wa, karena ditemukan bahwa uji t = -14.930 > t table 5 % = 2,262, maka dapat dikatakan bahwa t hitung > t table.The purpose of the study is to (1) find out the implementation of group counseling services to increase students’ emotional intelligence, (2) find out the model of the group counseling with effective simulation techniques to enhance the emotional in-telligence of students, (3) determine the level of effectiveness of group counseling models with simulation techniques to enhance the emotional intelligence of students. This study used a research design development stages as follow: (1) Preliminary studies, (2) Planning, (3) The development of hypothetical models, (4) Review of the hypothetical model, (5) Revision, (6) Limited trial to the group counseling model with simulation techniques to increase emotional intelligence. The subject of the test was students of Grade VII of SMP N 2 Bae Kudus Academic Year 2010/2011. Technically, it was done as follow: descriptive analysis method, collaborative partic-ipatory methods, and Quasi-experimental methods. General results in this study indicated that the model of group counseling with the simulation techniques was effective to enhance the emotional intelligence of stu-dents, because it was found out that t test = -14 930> t table 5% = 2.262. It can be said that the t count> t table.